Structural and morphological modification of the PEO coating on the Ti-25Ta-10Zr-15Nb alloy through heat treatment - Kuroda, Pedro A.B.; Cardoso, Giovana C. [UNESP]; Rossi, Mariana C.; Afonso, Conrado R.M.; Grandini, Carlos R. [UNESP] (Elsevier, 2024)
This study aims to produce a Plasma Electrolytic Oxidation (PEO) layer on the Ti-25Ta-10Zr-15Nb alloy (TTZN) and analyze the influence of heat treatment at different temperatures without a controlled atmosphere to promote thermal oxidation, and in a vacuum (10−7 Torr), to prevent oxidation. The results showed that the PEO coating was initially amorphous, and heat treatments promoted the formation of crystalline compounds. Raising the heat treatment temperature led to higher surface roughness in all conditions. The heat treatment under vacuum reduced thickness (9 → 4 μm), while the heat treatment in air promoted a thickness increasing (10 → 174 μm) and decreased the wettability (82 → 25°) of the oxide layer. Due to oxygen diffusion, there was an increase in the hardness of the TTZN alloy at the oxide/metal interface after heat treatment in the air (268 → 504 HV, 268 → 845 HV, and 268 → 1011 HV, at 800, 1000, and 1200 °C).
Keywords: PEO; Surface characterization; TTZN alloy